Association between individual ovarian dimensions with ovarian reserve indices - Naeini, Elham Hashemian (EXCLI J, 2013)
Introduction: In some young female candidates of assisted reproductive technology (ART), ovarian response to simulative treatments is less than what is expected. More precise assessment of oocyte quality and quantity through studying ovarian dimensions can be useful for determining the dose of ovarian stimulant drugs and for preventing ART cycles cancellation. The aim of the present study is to determine the association between ovarian dimensions and ovarian reserve (OR) indices and whether ovarian dimensions can predict ovarian reserve. Methods: In this cross-sectional study, 85 infertile women were studied. In early follicular phase, ovarian diameters (including length and width of the ovaries) were measured using transvaginal ultrasonography. Mean ovarian diameters (MOD) were calculated according to average length and width of the ovaries. A serum sample was taken from all patients to measure the level of Follicular Stimulating Hormone (FSH) and oestradiol as OR indices. Results: The results of univariate analysis showed that FSH and oestradiol had a negative significant association with width, length and MOD (P < 0.01). The results of multivariate regression analysis showed that FSH and oestradiol had a negative significant association with width (β(FSH) = -0.59, P = 0.001 and β(Oestradiol) = -0.019, P = 0.029) and MOD (β(FSH) = -0.52, P = 0.003 and β(Oestradiol) = -0.021, P = 0.017) and had a borderline negative significant correlation with ovarian length (β(FSH) = -0.49, P=0.077 and β(Oestradiol) = 0.022, P = 0.08) Conclusions: The results of this study revealed that despite a moderate correlation, ovarian diameters could be an applicable index for predicting OR. Using this method along with other methods may be useful in treatment with ovarian stimulants.